Clinical and Immunological Insights into Oral Candidiasis: Candida Biofilms and Host Cytokine Responses, Koya-Iraq - Mirkhan, Sawan M.; Zrary, Taha J. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Oral candidiasis (OC) is a widespread opportunistic fungal disease primarily caused by Candida albicans, with non-albicans Candida species progressively recognized as new pathogens. Previous studies have typically focused on a single microbial feature, such as the frequency of Candida species or biofilm formation, or on host immune responses, including cytokine activity, but have rarely investigated both simultaneously. These gaps have limited understanding of how fungal virulence factors interact with host immunity and have hindered the identification of reliable disease biomarkers. The present investigation examined the prevalence, species distribution, biofilm activity, and host immune responses in OC participants in Kurdistan, Iraq. A total of 154 suspected cases were directly cultured on Sabouraud Dextrose Agar and HiCrome™ Candida Differential agar and analyzed with the VITEK 2 system. Among them, 61 participants (39.6%) tested positive for OC, with C. albicans as the predominant isolate (59.4%), followed by Candida kefyr, Candida dubliniensis, Candida parapsilosis, Candida tropicalis, and Candida krusei. More than half of the isolates produced biofilm, and C. tropicalis exhibited the strongest biofilm-forming capacity. Immunological profiling revealed significantly higher neutrophil counts and elevated serum interleukin (IL)-10 and IL-17 in OC-positive participants. Diabetes mellitus appeared as the most common comorbidity. By integrating Candida species characterization with host immune profiling, this research provides new insights into the interaction between host defense mechanisms and fungal pathogenicity. In contrast to earlier work, the current analysis directly related species-specific biofilm capacity with neutrophil and cytokine dynamics, establishing IL-17 as a potential biomarker of OC activity.